Prevalence, pattern and predictors of hearing loss among rural school-age children in Ogun State, Nigeria (2016)
Background: Hearing loss is one of the commonest and most neglected disabilities in developing countries. However, most of these are preventable with early detection through screening and appropriate interventions. Methods: We determined the prevalence, pattern and predictors of hearing loss in school aged children in selected rural communities in Ogun state, Nigeria, using a cross sectional study design. A multistage cluster sampling technique was used to select 305 pupils from 6 randomly selected primary schools. Semi-structured interviewer administered questionnaires and a calibrated Amplivox 240 diagnostic audiometer were used for data collection. Multiple logistic regression analysis was used to determine the risk factors. Results: The prevalence of bilateral hearing loss was 19.6% while unilateral hearing loss was 11.8% on the left side and 7.9% on the right.Low frequency hearing lossconstituted the commoner type of hearing loss with [54(64.3%)] occurring on the right and [69 (71.1%)] on the left. Logistic regression analysis revealed that history of ear discharge (OR= 2.80, 95% CI= 1.23-6.38: p=0.006), ear injury (OR= 2.28, 95% CI= 1.09-4.74: p=0.028), head trauma (OR= 4.54, 95% CI= 1.97-10.44: p